Mortuary dialogues : death ritual and the reproduction of moral community in Pacific modernities - Lipset, David, 1951-; Silverman, Eric Kline (ASAO studies in Pacific anthropology, 2016)
Mortuary Dialogues presents fresh perspectives on death and mourning across the Pacific Islands. Through a set of rich ethnographies, the book examines how funerals and death rituals give rise to discourse and debate about sustaining moral personhood and community amid modernity and its enormous transformations. The book's key concept, "mortuary dialogue," describes the different genres of talk and expressive culture through which people struggle to restore individual and collective order in the aftermath of death in the contemporary Pacific.